2023
DOI: 10.1007/s10689-023-00328-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of familial pancreatic cancer families with additional colorectal carcinoma

Abstract: Familial pancreatic cancer (FPC) is a rare hereditary tumor entity with broad phenotypic heterogeneity, including colorectal carcinoma (CRC) in some families. The underlying factors for this co-occurrence are still not well evaluated. FPC families in the National Case Collection of Familial Pancreatic Cancer with an additional occurrence of CRC were analyzed regarding the phenotype, genotype and recommendation for a clinical screening program. The total cohort of 272 FPC families included 30 (11%) families wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
0
0
Order By: Relevance
“…However, the genetic predisposition for many FPC families is still unknown [101]. Hence, in order to focus the gene discovery on those FPC families, for which the predisposing genetic background is unknown, we excluded families having at least one known predisposing genetic mutation in the gene set including BRCA2, PALB2, CDNK2a, SUFU, and CHEK2 (see also [101,102] for more details about the mutation screening panel). Individuals of an FPC family that solely had BC were marked as "unknown" because it has been shown that BC and PC have a common causal pathway, mediated, e.g., by BRCA1/2 or PALB2 mutations [103].…”
Section: Analysis Of Fapaca Familiesmentioning
confidence: 99%
“…However, the genetic predisposition for many FPC families is still unknown [101]. Hence, in order to focus the gene discovery on those FPC families, for which the predisposing genetic background is unknown, we excluded families having at least one known predisposing genetic mutation in the gene set including BRCA2, PALB2, CDNK2a, SUFU, and CHEK2 (see also [101,102] for more details about the mutation screening panel). Individuals of an FPC family that solely had BC were marked as "unknown" because it has been shown that BC and PC have a common causal pathway, mediated, e.g., by BRCA1/2 or PALB2 mutations [103].…”
Section: Analysis Of Fapaca Familiesmentioning
confidence: 99%